2020
DOI: 10.18203/2320-6012.ijrms20201490
|View full text |Cite
|
Sign up to set email alerts
|

The role of neutrophil/lymphocyte ratio in predicting the severity of sepsis in a tertiary care hospital in South India: a retrospective study

Abstract: Background: Sepsis, a syndrome of dysregulated host response to infection leading to life-threatening organ dysfunction, is having a substantial burden in health system. The outcome in sepsis is often time dependent. None of the clinical manifestations nor the age-old markers like ESR, CRP, etc. have proven diagnostic or prognostic of sepsis. This study aims to assess the role of neutrophil: lymphocyte ratio (NLR) in assessing the severity of sepsis within the initial 24 hrs of admission. Methods: Authors did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In the study conducted by George et al, 78.4% of sepsis patients with NLCR score >5 were associated with more than two organ dysfunctions. 19 Rehman et al, in their study, stated that NLCR is comparable with other sepsis biomarkers (CRP, procalcitonin, and sequential organ failure assessment score) as a marker of disease severity. 20 Hence, a higher NLCR score can be used to initiate robust empirical therapy in patients with sepsis.…”
Section: Discussionmentioning
confidence: 91%
“…In the study conducted by George et al, 78.4% of sepsis patients with NLCR score >5 were associated with more than two organ dysfunctions. 19 Rehman et al, in their study, stated that NLCR is comparable with other sepsis biomarkers (CRP, procalcitonin, and sequential organ failure assessment score) as a marker of disease severity. 20 Hence, a higher NLCR score can be used to initiate robust empirical therapy in patients with sepsis.…”
Section: Discussionmentioning
confidence: 91%
“…They discovered that there most septic patients with MODS had a high NLR. The ratio is deemed superior to a white blood cell count [26] . A study with a large sample size by Li et al in 2016 also showed the predictive capability of NLR in septic patients [27] .…”
Section: Discussionmentioning
confidence: 99%
“… 5–8 The increase in the concentration of these biomarkers can suggest the occurrence of sepsis and the clinicians will be able to initiate the appropriate and early treatment and thus the mortality in sepsis could be significantly reduced. 9 …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] The increase in the concentration of these biomarkers can suggest the occurrence of sepsis and the clinicians will be able to initiate the appropriate and early treatment and thus the mortality in sepsis could be significantly reduced. 9 PCT is the most frequently investigated biomarker of sepsis and has demonstrated the best reliability in early diagnosis, especially for the detection of bacterial infections, compared to other inflammatory biomarkers. 10,11 However, many studies recommend the association of PCT with other inflammatory biomarkers for increasing the reliability in early diagnosis.…”
Section: Introductionmentioning
confidence: 99%